PTU-118 An audit of the prevalence of chronic hepatitis c and treatment outcomes in drug users attending substance misuse centres in bradford – planning for future service provision. (22nd June 2015) - Appleby, VJ; Darnbrough, E; Forrester, K; Simpson, R; Clarke, C; Moreea, S
Abstract : Introduction: Injecting drug use including indirect sharing of drugs and preparation equipment is the most common mode of hepatitis C (HCV) transmission in the developed world. The prevalence of HCV in injecting drug users is between 64–94%. 1 HCV treatment (Tx) in this group is low for a number of well documented reasons. We wanted to establish the number of service users (SU) registered and attending three substance misuse centres in Bradford. We also wanted to establish the prevalence of HCV in this population. Secondary outcomes included determining the frequency of different genotypes and the outcome of referrals made to Viral Hepatitis Services (VHS) in secondary care. Method: The electronic records of all SU were reviewed to establish the results of HCV screening. The VHS database was then interrogated to determine assessment (Axe) and Tx outcomes. Results: 558 SU attended unit 1:(506 (91%) males (M); 52 (9%) females (F)). 372 (67%) were antibody negative (AB –ve), 133 (24%) (115M, 18F) were PCR positive (PCR +ve), 29 (5%) antibody positive/PCR negative (AB +ve/PCR –ve) and 24 (4%) had never been screened (NS). 63/133 (47%) had been Axe for Tx, 70/133 (53%) had not been referred to VHS. 47/63 (75%) were suitable for Tx, 16 (25%) either did not attend Axe or had outstanding psycho-social issues delaying Tx. In the Tx group, 25 (53%) had a six month (6/12) sustained virological response (SVR) (14 genotype (G)1, 2G2, 9G3). 13 (28%) stop/failed Tx, 6 (13%) were awaiting (aw) SVR (4G3, 1G2, 1G1) and 3 (6%) were still on Tx (all G3). 536 SU (315 (59%) M; 221 (41%) F) attended unit 2.354 (66%) were AB –ve, 69 (43F, 26M) PCR +ve, 42 (8%) AB+ve/PCR –ve and 71 (13%) had NS. 21/69 (30%) had been assessed for Tx, 48 (70%) not yet referred. 14 (67%) were suitable and 7 (33%) had Tx delayed. In the Tx group 10 (72%) had 6/12 SVR (6G1, 4G2); 2 (14%) stop/failed tx (1G1, 1G3); 1 G1 (7%) aw SVR; 1 G1 (7%) still on tx. 230 SU (167M (73%); 63F (27%)) attended unit 3. 152 (67%) AB –ve, 41 (35M, 6F) PCR +ve, 23 (10%) AB+ve/PCR –ve, 13 (6%) NS. 20/41 (49%) had undergone Axe, 21 (51%) not referred. 12 (60%) were suitable for Tx, 8 (40%) had Tx delays. In the Tx group, 8 (67%) had 6/12 SVR (6G1, 2G3); no-one failed tx; 3 (25%) still on tx (2G3, 1G1); 1 G1 (8%) a/w SVR. Conclusion: The prevalence of chronic HCV was much lower than predicted. We identified that high numbers of patients are not currently been referred for assessment in secondary care. Increasing community based assessment and treatment services may help to address this problem Disclosure of interest: None Declared. Reference: Grebely J. Management of HCV and HIV infections among people who inject drugs. Curr Opin HIV AIDS 2011;6(6): 501–507